2015
DOI: 10.1186/s12937-015-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent diagnosis of acute malnutrition by weight-for-height and mid-upper arm circumference: contributors in 16 cross-sectional surveys from South Sudan, the Philippines, Chad, and Bangladesh

Abstract: BackgroundThe two anthropometric indicators of acute malnutrition in children under 5 years, i.e. a Mid-Upper Arm Circumference < 125 mm (MUAC125) or a Weight-for-Height Z-score<−2 (WHZ−2), correlate poorly. We aimed at assessing the contribution of age, sex, stunting (Height-for-Age HAZ<−2), and low sitting-standing height ratio Z-score (SSRZ in the 1st tertile of the study population, called hereafter ‘longer legs’) to this diagnosis discrepancy.MethodsData from 16 cross-sectional nutritional surveys carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
46
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 15 publications
12
46
2
Order By: Relevance
“…The available data suggests that the limbs of these latter children are not proportionately long and at least for these populations variation in limb length is an inadequate explanation for the much greater proportion of children diagnosed by WHZ and not by MUAC. This conclusion is supported by an analysis by Roberfroid et al [26]. They examined the relationship between WHZ and MUAC from 16 surveys in which sitting height had been measured and concluded that leg length had a minor effect upon the discrepancy and that other factors were dominant.…”
Section: Discussionsupporting
confidence: 55%
“…The available data suggests that the limbs of these latter children are not proportionately long and at least for these populations variation in limb length is an inadequate explanation for the much greater proportion of children diagnosed by WHZ and not by MUAC. This conclusion is supported by an analysis by Roberfroid et al [26]. They examined the relationship between WHZ and MUAC from 16 surveys in which sitting height had been measured and concluded that leg length had a minor effect upon the discrepancy and that other factors were dominant.…”
Section: Discussionsupporting
confidence: 55%
“…Briend et al misquote our paper and consistently misquote Roberfroid et al's paper [34,35,49] which both show that long-legs have a minor effect on WHZ which is inadequate to explain the discrepancies between WHZ and MUAC in diagnosing SAM. There are many societies shown in our paper where long-legs cannot be the cause for the dramatic discrepancy between MUAC-SAM and WHZ-SAM.…”
Section: Assertion 3: Children Who Have a Low Whz Are Relatively Healmentioning
confidence: 61%
“…There are a number of studies that demonstrate the lack of clear agreement between anthropometric indices for identifying malnutrition. Specifically, BMI, WL, and MUAC tend to identify different proportions of children with malnutrition . This may be explained, in part, because the majority of studies mix comparisons between age‐specific/gender‐specific criteria (WLz or BMIz) and absolute value based‐criteria (MUAC in centimeters), though it is well supported that z ‐score‐based classifications are accompanied by greater sensitivity and less bias than absolute value cutoffs .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, BMI, WL, and MUAC tend to identify different proportions of children with malnutrition. 18,19 This may be explained, in part, because the majority of studies mix comparisons between age-specific/gender-specific criteria (WLz or BMIz) and absolute value based-criteria (MUAC in centimeters), though it is well supported that z-score-based classifications are accompanied by greater sensitivity and less bias than absolute value cutoffs. 8,[20][21][22][23][24][25][26][27] In a 2014 consensus document, AND/ASPEN thoughtfully recommended indicators of pediatric malnutrition that were evidence based, inexpensive, easy to use, reproducible, and sensitive for both screening and longitudinal monitoring.…”
Section: Discussionmentioning
confidence: 99%